2008
DOI: 10.1016/j.acalib.2008.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy and Reflective Pedagogical Praxis

Abstract: Drawing on discussions within Composition and Rhetoric, this article examines information literacy pedagogy. It considers how academic librarians can work toward theorizing our profession in such a way that we may ask new questions of it and foster creative, reflective and critical habits of mind regarding pedagogical praxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 6 publications
0
69
0
6
Order By: Relevance
“…We agree with Jacobs [25] who claims that "instructional strategies and techniques are an important part of teaching but they must be informed by an understanding of pedagogical theory" [p. 257]. Therefore, we claim that it is not sufficient to base only on information and media practices while designing educational materials.…”
Section: Discussionmentioning
confidence: 48%
“…We agree with Jacobs [25] who claims that "instructional strategies and techniques are an important part of teaching but they must be informed by an understanding of pedagogical theory" [p. 257]. Therefore, we claim that it is not sufficient to base only on information and media practices while designing educational materials.…”
Section: Discussionmentioning
confidence: 48%
“…Are they confident in and prepared for pedagogical work? A study conducted by Heidi on Masters of Library and Information Science (MLIS) programmes revealed that very few LIS schools provide preparation in instructional and pedagogical skills because pedagogy and instruction do not occupy the same status as reference, cataloguing, collection development and other core LIS skills (Jacobs 2008). The critical question is: if LIS education does not include the component of education and training, where will graduates gain instructional expertise?…”
Section: Teaching User Education: Caveats and Considerationsmentioning
confidence: 99%
“…The critical question is: if LIS education does not include the component of education and training, where will graduates gain instructional expertise? Elmborg (2006) and Jacobs (2008) advocate for the transformation of LIS education and training by incorporating into the curriculum basics of methods of instruction and teaching styles (Jacobs 2008;Saunders 2002) as well as pedagogical theory (Elmborg 2006). This proposed inclusion may enhance the librarians' sense of preparedness in their instructional roles (Jacobs 2008).…”
Section: Teaching User Education: Caveats and Considerationsmentioning
confidence: 99%
“…Following in Pawley's footsteps, several writers have examined the relationship between neoliberalism and "mainstream" information literacy research and commentary (e.g., the ACRL Standards) (Seale 2013(Seale , 2015 and how most information literacy "embraces a skills agenda" that views students as "entrepreneurs of the self" who must adapt to a precarious work life after university (Nicholson 2015). The term critical information literacy gained prominence with James Elmborg's (2006) Critical Information Literacy: Implications for Instructional Practice, and was followed by works such as Jacobs (2008) and the publication of the edited book collection Critical Library Instruction: Theories and Methods (Accardi, Drabinski, & Kumbier, 2010). Since 2010, a number of works, conferences, meetings, and web chats have advocated a more critical approach to librarianship (e.g., works such as Feminist Pedagogy for Library Instruction, the use of #critlib on Twitter).…”
Section: Copementioning
confidence: 99%